The Effect of Progressive Muscle Relaxation on Anxiety Levels Facing Labor in Pregnant Women in the Third Trimester - Hidayatin, Nur; Anitarini, Fany; Kusumawati, Diana; Izzah, Ukhtul; Christiana, Indah; Wati, Ni Ketut Ratna Diana (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Anxiety is one of the psychological disorders that can occur among third-trimester pregnant. Progressive muscle relaxation therapy represents a potential intervention for alleviating anxiety. This research aimed to determine the impact of this therapy on anxiety levels in expectant mothersin the third trimester.This study is a pre-experimental study with a one-group pre and post- test design. Thesample used was 28 pregnant women in the third trimester chosen through a purposive sampling technique.The variables studied were anxiety level in facing childbirth and progressive muscle relaxation.The measuring instruments used were the SOP progressive muscle relaxation and the PerinatalAnxiety Screening Scale (PASS) questionnaire. The hypothesis test used was Wilcoxon in IBMSPSS Statistic 26.Prior to the intervention, the majority of respondents (71.4%, n=20) reported experiencing moderate anxiety. Following the intervention, a substantial shift was observed, with nearly all respondents (89.3%, n=25) exhibiting mild anxiety.There was a decrease in anxiety scores from 24.61 to 15.5. Based on the Wilcoxon analysis, therewas an effect of progressive muscle relaxation on anxiety in facing childbirth with an Asymp. Sig. (2-tailed) value of 0.000 (<0.05).The efficacy of progressive muscle relaxation in alleviating childbirth-related anxiety among pregnant women has been conclusively demonstrated. Each progressive muscle relaxation movement provides a relaxing effect onevery muscle in the body. Pregnant women can apply this therapy independently to reduce anxiety.